OPPORTUNITIES FOR APPLYING INFORMATION AND COMMUNICATION TECHNOLOGIES (Scientific journal of the Fergana State University, 2026)
This article highlights the significant potential of information and communication technologies (ICT) for improving educational processes. During the conducted experiment, an ICT-based interactive learning module was integrated into the curriculum, and its impact on students’ learning outcomes and engagement was evaluated.The experiment was implemented using a pretest–posttest design and through collecting student feedback via a survey. The results showed a substantial improvement in academic performance, with average test scores increasing from 56% to 70%.Student feedback was also highly positive: more than 90% of participants reported that ICT tools made the learning process more interesting and more effective. In addition, the article discusses the importance of ensuring effective implementation of ICT and providing equal opportunities in its integration.